ENHANCING THE COMMUNICATION SKILLS AMONG HOTEL EMPLOYEES: THE INTRODUCTION OF MIND MAP TECHNIQUE - Shu, Efin (Faculty of Economics and Business Universitas Pelita Harapan, 2024)
Communication skills are essential in the Hospitality industry as the industry mainly deals with people. When communication is handled properly, it will develop guests’ loyalty toward the hotel brand. However, communication is usually challenging, especially during busy operational hours. Messages might not be delivered comprehensively at the right time due to employees’ forgetfulness. Therefore, this community service aims to introduce the mind map technique to the Hotel employees, to enhance remembering, and to assist in organizing their daily tasks better. The method used in this community service is providing training to explain the technique, continuing with a mind map exercise, and ending with group presentations. From the training, the employees had gained more understanding about the technique. They felt that the technique was able to answer their needs related to effective communication and had a real and positive impact on them. The mind map technique is expected to be implemented daily by the Hotel employees so that the communication process will be improved.